(untitled) (Surkhet Journal, 2025)
This study examines the physical and psychological impacts of the 2023 earthquake in Jajarkot district on children. Using a mixed research design, 110 households with at least one child affected by the disaster were selected through purposive sampling. Primary data were gathered through structured and unstructured interviews with household heads. The study reveals that physical outcomes were notably severe, with 30 cases of death, 19 amputations, 16 disabilities, and 10 injuries reported. Psychologically, anxiety was the most prevalent condition (30 cases), followed by depression and fear (20 each), isolation and insomnia (12 each), aggressiveness (10), and concentration difficulties (6). These findings underscore the vulnerability of children during natural disasters. The study further highlights the urgent need for child-specific emergency medical care and psychosomatic support within disaster management systems. By investigating the direct and long-term effects, of the earthquake on children’s health, the study provides essential insights for policymakers, healthcare providers, and educational institutions to develop child-centered strategies for disaster recovery. The research also emphasizes the importance of addressing both physical injuries and mental health challenges, which are often overlooked in disaster response, thereby ensuring a holistic approach to child welfare in disaster-prone regions. This study contributes to the creation of targeted programs to safeguard children’s health and development during and after natural disasters, ensuring a comprehensive recovery process.